An investigation of the problems primary teachers face in the teaching of mathematics in the County of Victoria - Lalbeharry, Deodath (1990)
This study sought to ascertain the needs of practising primary teachers and the problems they face in teaching mathematics. A sample of 105 teachers from the County of Victoria in Trinidad were grouped on the basis of school location (urban, semi-urban, rural) and years of experience as trained teachers, and interviewed through a questionnaire. Data analysis showed that there was no significant difference in the frequency and intensity of problems teachers experienced across school location. The school system was generally perceived to be unsupportive of teachers' classroom efforts. Generally, the mathematics syllabus did not present problems, though it was too wide to be completed in the given time. Some teachers reported having problems with certain topics and with teaching methods. Their greatest problem seemed to be their students' lack of readiness to pursue upper school studies. The more experienced teachers faced problems significantly less frequently and less intensely than their less experienced counterparts
Keywords: Primary school mathematics